Effect of Closed and Opened the Door to Temperature on PID-Based Baby Incubator with Kangaroo Mode - Vanda Catur Kirana; Dwi Herry Andayani; Andjar Pudji (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2021)
The uneven distribution of the baby incubator temperature can cause the temperature in the baby incubator to be different at each point. The purpose of this study was to analyze the effect of the door closed and opened to the temperature at each point of sensor placement that has been determined. The study was conducted as an experimental research design. In this experiment, an Incu Analyzer comparison was used as a calibrator unit, a baby skin temperature thermistor sensor, and four LM35 sensors for baby incubator room temperature with one LM35 sensor as a PID control system carried out by trial-and-error method. Based on the results of measurements was made with the design, when the chamber is open, it produces an average error value of T1 4.083%, T2 6.06%, T3 3.78%, T4 4.88%, and T5 1.48%, while when the chamber is closed, it produces an average error value T1 0.75. %, T2 0.88%, T3 1.15%, T4 0.74%, and T5 0.87%. Measurement of skin temperature using a thermometer has an average error value of 1.1%. The results showed that uneven heat transfer, lack of air distribution, different sensor placements at each point, and non-standard chamber sizes were factors that were uneven at each point. Based on the results of the study, it was found that the use of a working system on this device can be implemented to control the temperature of the baby incubator by knowing the temperature distribution at each point